The Epistemology of Transformative Learning: A Systematic Instructional Design Framework Model in Transformative Learning - Ubaidah Ubaidah; Nurdin Ibrahim; Eveline Siregar (International Journal of Multi Discipline Science, 2023)
Research in transformative learning has flourished in educational research in the latest decades. Among the research on transformative learning, the specific topic of how to develop instruction based on transformative learning is still very rarely found. The purpose of this study was to review the epistemology of transformative learning by introducing a systematic ID framework for transformative learning. The method of this study was the systematic literature review with three review stages: planning the review, conducting the review, and reporting the review. The review was focused on the academic paper in the research scope of transformative learning. As the result, we concluded the 3 main components of designing a transformative learning model: (1) transformative outcomes, (2) transformative scaffolding, and (3) transformative learning experience. The study also proposed 7 stages of systematic ID framework in designing transformative learning.